A1: Clinical Inactive Disease in the Pediatric Rheumatology Care and Outcomes Improvement Network Cohort: Which Components of Clinical Inactive Disease Do Patients Not Achieve?. Issue 11 (March 2014) - Bingham, Catherine A.; Ardoin, Stacy P.; Vora, Sheetal S.; Darbie, Lynn M.; Lovell, Daniel J.; Weiss, Jennifer E.; Laxer, Ronald M.; Olson, Judyann C.; Passo, Murray H.; Gottlieb, Beth S.; Stock, Jason A.; DeWitt, Esi Morganv
Abstract : Background/Purpose: The American College of Rheumatology (ACR) provisional criteria for Clinical Inactive Disease (CID) are an accepted outcome measure for juvenile idiopathic arthritis (JIA) patients (1 ). The purpose of this study is to determine what components of CID are not met by Pediatric Rheumatology Care and Outcomes Improvement Network (PR–COIN) patients. The goal is to better understand the ways in which patients are not doing well. We hypothesize that many patients who do not meet CID have mild disease activity such as joint count <3, physician global assessment of disease activity score of <3, or short duration of morning stiffness, but otherwise would fulfill CID. Methods: PR‐COIN is a multi‐center quality improvement learning network comprised of 11 sites in North America whose mission is to improve outcomes for children with JIA. With IRB consent, patient data are entered into the ACR's Rheumatology Clinical Registry. The criteria for CID include the following: no joints with active arthritis, no systemic features, no active uveitis, normal ESR or CRP (if measured), physician global assessment of disease activity of 0, and duration of morning stiffness < 15 min (1 ). Data were analyzed to determine which components of CID patients do not achieve. Only patients with complete data such that CID status could be calculated were included. Results: Data from 658 individual patients were analyzed. Sixty‐one percent of patients did not achieve clinical inactive disease at their most recent visit (404/ 658 patients). The top 3 components of clinical inactive disease that patients did not meet, from most frequent to least frequent, were physician global assessment (91%), joint count (66%), and duration of morning stiffness (28%). Of the patients with active disease, sixteen percent had elevated ESR or CRP (inflammatory markers were not measured in all patients), 11% had active uveitis, and <1% had active systemic JIA features. Sixty‐two percent of patients with active disease had a joint count <3, physician global assessment <3, and duration of morning stiffness < 30 minutes, perhaps indicating this was a subset of patients with mild disease activity. This represents 38% of the total population. Thus, 77% of PR‐COIN patients had clinical inactive disease or mild disease. Seven percent had active uveitis. Conclusion: Although only 39% of patients achieve CID at their most recent visit in the PR‐COIN cohort, and this falls short of our desired outcome, many of these patients with active disease appear to have only mild disease activity. Therefore, the ACR criteria for CID may be somewhat stringent and difficult to achieve in the clinical setting. CID being a binary "all or none" outcome measure makes it difficult to detect whether quality improvement activities are having any beneficial incremental impact on patient disease status. PR‐COIN will continue to seek ways to improve rates of CID.